2006
DOI: 10.1126/science.1130726
|View full text |Cite
|
Sign up to set email alerts
|

Washing Away Your Sins: Threatened Morality and Physical Cleansing

Abstract: Physical cleansing has been a focal element in religious ceremonies for thousands of years. The prevalence of this practice suggests a psychological association between bodily purity and moral purity. In three studies, we explored what we call the "Macbeth effect"-that is, a threat to one's moral purity induces the need to cleanse oneself. This effect revealed itself through an increased mental accessibility of cleansing-related concepts, a greater desire for cleansing products, and a greater likelihood of tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
835
9
14

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 922 publications
(902 citation statements)
references
References 5 publications
44
835
9
14
Order By: Relevance
“…Because each of these actions is aimed at achieving the same goal of relief from self-recrimination, it is possible that they could serve as substitutes for one another. There is some evidence for the interchangeability of these actions already- Zhong and Liljenquist (2006) showed that that washing one's hands after recalling a bad deed diminished participants' willingness to help a needy student. If the different ways of dampening self-recrimination all work to some degree, are some means preferred over others?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because each of these actions is aimed at achieving the same goal of relief from self-recrimination, it is possible that they could serve as substitutes for one another. There is some evidence for the interchangeability of these actions already- Zhong and Liljenquist (2006) showed that that washing one's hands after recalling a bad deed diminished participants' willingness to help a needy student. If the different ways of dampening self-recrimination all work to some degree, are some means preferred over others?…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences for the other three emotions, all ps > .19. 3 In an effort to reduce suspicion, we asked participants to write about a time they had done something unethical (see Zhong & Liljenquist, 2006), rather than the time they felt "most guilty. "…”
Section: Endnotesmentioning
confidence: 99%
See 1 more Smart Citation
“…While both questionnaires mixed guilt items with other items, an explicit measure of guilt may induce suspicion in participants and thus trigger demand characteristics or social desirability effects (Schwarz & Oyserman, 2004). Future studies should also incorporate implicit measures of guilt (Zhong & Liljenquist, 2006). Additionally, retrospective questionnaires may be prone to bias, particularly when seeking to assess the intensity or frequency of human experiences (Schwarz & Oyserman, 2004).…”
Section: Running Head: Virtual Violence and Guilt 21mentioning
confidence: 99%
“…Other studies have revealed that morality and cleanliness are strongly related. Thinking about an unethical deed makes cleaning related words more accessible and reading an unethical story increases the desire for cleaning related products (Zhong & Liljenquist, 2006). Activating the concept of cleanliness before reading moral dilemmas, as well as washing ones hands after seeing a disgusting movie clip, reduces the severity of moral judgments (Schnall, Benton, & Harvey, 2008).…”
Section: Moralitymentioning
confidence: 99%